Analisis Investasi Sistem Penyediaan Air Minum Kota Dumai Berdasarkan Kerjasama Pemerintah Dan Swasta - Jhon Hadi Kusuma; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Construction of water supply system has been implemented Dumai City since 2009. But until 2011 the construction should be done despite stalled cost as much as Rp 180 billion. The cost is only partially physical labor can build transmission and distribution networks in 4 districts. Therefore, the city government plans to continue the development dumai the project. In the government's development plan includes an investor to reduce sourced financing from the state budget. In this study, the system will analyze the cooperation undertaken by making 3 schemes. And each of these schemes will be analyzed in the economy that is based on net present value (NPV), internal rate of return (IRR),  benefit cost ratio (BCR), and payback period (PBP). Economic analysis is performed on each scheme can be stated that the three schemes is feasible, for each of the parameters such as NPV is positive, BCR greater than 1.0 and internal rate of return and the value of the prevailing commercial interest, but the rates obtained are very expensive so the rates are not feasible. but the rates obtained are very expensive so the rates are not feasible. Thus, in the financing of infrastructure development should be done budget sharing the rates obtained becomes smaller.  Keyword: water supply system, investment, NPV, BCR, IRR, PBP